Using theory-based evaluation to understand what works in asset-based community development. (29th October 2021) - Ward, Sarah
Abstract: Asset-based community development (ABCD) has become a popular approach to community work, with the claim that it can support high poverty communities to drive the process of community development. Yet there is little detailed evidence on the efficacy of the ABCD model, and how this relates to the political, economic, and social context in which the intervention is located. This article presents research from a community case study in Scotland to explore how Theory-Based Evaluation can clarify ABCD's hypothesis for change. Understanding ABCD's causal mechanisms allows a nuanced consideration of why it may have limited impact and highlights the importance of context when planning community interventions. The study demonstrates that ABCD can generate locally led activity and build social networks but is unlikely to achieve a 'tipping point' from activity generation into wider community association without pre-existing resources being in place. Community association relies on pathways of activism that support local action incrementally and require resources in support of this.